Acupuncture for Psychosomatic Symptoms of Hwa-byung, an Anger Syndrome: A Feasibility Randomized Controlled Trial - Choi, Yujin; Park, In-Hye; Kim, Jung-Eun; Kwon, Ojin; Kim, Ae-Ran; Park, Hyo-Ju; Lee, Jun-Hwan; Kim, Joo-Hee (Frontiers in Psychology, 2021)
Objectives: Emerging studies found the potential effects of acupuncture for treating chronic pain and mental disorders, including depressive and anxiety disorders. Acupuncture is widely used for treating culture-related anger syndrome, Hwa-byung. This pilot trial aimed to investigate the feasibility of a clinical trial testing acupuncture for the psychosomatic symptoms of Hwa-byung. Methods: Twenty-six patients with Hwa-byung planned to be randomly assigned to the acupuncture or sham acupuncture groups. Ten treatment sessions were applied over four weeks. The 100 mm visual analog scale was used to measure the six major Hwa-byung symptoms: stuffiness in the chest, heat-sensations, pushing-up in the chest, feeling a mass in the throat, feelings of unfairness, and hard feelings. The criteria for assessing the success of this pilot trial were defined as improvement in three or more of the six Hwa-byung symptoms after treatment, with an effect size greater than 0.2. Results: Fifteen patients were finally included and randomly assigned to the acupuncture (n = 7) or the sham acupuncture group (n = 8). After 10 treatment sessions, Cohens’d effect sizes for acupuncture compared to sham acupuncture were greater than 0.2 for each one of the six major Hwa-byung symptoms, which met our a priori criteria for success. Also, the effect size for the somatic symptoms of ‘stuffiness in the chest’ was 0.81 (95% CI -0.40, 2.20), referring to a large effect size. Conclusions: Our results suggest that acupuncture treatment would be regarded as an acceptable intervention for a full-scale study of psychosomatic symptoms in Hwa-byung patients.